Real-World Comparison of Predictive Controllers Based on Internal and External Description of the Controlled System - Honc, Daniel; Novotný, Aleš (Springer Nature Switzerland AG, 2024)
Predictive control is a very general method of designing an optimal controller, allowing the use of different criteria, but also a large number of different models of the controlled system. In this paper, the derivation and real application of two types of predictive controller are shown - for internal description (expressed by a discrete-time state-space model) and for external description (expressed by discrete-time transfer function). In an ideal simulation both controllers give identical results, but in real conditions different behavior will be displayed. The aim of this paper is to demonstrate the differences between the two solutions from an application point of view, to discuss the strengths and weaknesses of both types of predictive controllers and to compare their behavior in real conditions. The result is not the “best” controller but understanding their differences and facilitating the selection of the right form for a specific application.
Porovnání prediktivních regulátorů v reálném provozu na základě vnitřního a vnějšího popisu řízeného systému
Keywords: DC Motor Speed Control; Predictive Controller; State-space Model; Transfer Function; Řízení otáček stejnosměrného motoru; prediktivní regulátor; model stavového popisu; přenosová funkce